2018
DOI: 10.1016/j.neuroimage.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Time course of clinical change following neurofeedback

Abstract: Neurofeedback - learning to modulate brain function through real-time monitoring of current brain state - is both a powerful method to perturb and probe brain function and an exciting potential clinical tool. For neurofeedback effects to be useful clinically, they must persist. Here we examine the time course of symptom change following neurofeedback in two clinical populations, combining data from two ongoing neurofeedback studies. This analysis reveals a shared pattern of symptom change, in which symptoms co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
86
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 51 publications
14
86
4
2
Order By: Relevance
“…are more pronounced at follow-ups of at least 2 months (Megumi et al, 2015;Rance et al, 2018). This continued improvement after neurofeedback training has been demonstrated in as little time as 1 day (Harmelech et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…are more pronounced at follow-ups of at least 2 months (Megumi et al, 2015;Rance et al, 2018). This continued improvement after neurofeedback training has been demonstrated in as little time as 1 day (Harmelech et al, 2013).…”
Section: Discussionmentioning
confidence: 76%
“…This has also been used to downregulate craving in individuals with AUD (Karch et al, 2015) and obesity (Spetter et al, 2017), as well as smokers (Hartwell et al, 2016) and cocaine users (Kirschner et al, 2018). Other studies present individuals with stimuli that invoke anxiety, such as trauma-inducing words for patients with PTSD (Nicholson et al, 2017), contamination images for patients with OCD (Scheinost et al, 2013b;Rance et al, 2018), and pictures of spiders in females with spider phobia (Zilverstand et al, 2015). By practicing control of reactivity based on signal from the orbitofrontal cortex (OFC), dorsolateral prefrontal cortex (dlPFC), and insula, these patients had reduction in anxiety symptomology.…”
Section: Behavioral Domains Where Neurofeedback Has Been Investigatedmentioning
confidence: 99%
“…Evidence of delayed effects of neurofeedback emerging after the primary endpoint of a study has been reported. Particularly when investigating clinical populations, follow-up measures may boost statistical power and should be applied where possible (Rance et al, 2018;Van Doren et al, 2019).…”
Section: Follow-up Measuresmentioning
confidence: 99%
“…Identifying t the potential long-term effects of neurofeedback training on sustained reductions in substance use is essential in order for rtfMRI-nf to be used as a treatment modality for addiction. Emerging evidence suggests that rtfMRI-nf can indeed have lasting therapeutic effects on behavioral modification and symptom reduction ( Mehler et al, 2018 , Rance et al, 2018 ). Continued research that incorporates follow-up assessments on rtfMRI-nf learning effects is needed to validate the efficacy of neurofeedback training.…”
Section: Future Directions For Real-time Fmri Neurofeedback Researchmentioning
confidence: 99%